PERBANDINGAN TANGGUNG JAWAB DIREKSI BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 DENGAN UNDANG-UNDANG NOMOR 1 TAHUN 1995 TENTANG PERSEROAN TERBATAS - Ima Purnama Sari, Ida Ayu; Budi Arsika, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014, 2014)
This journal entitled "Comparison of Board of Directors Responsibilities Underthe Law Number 40 of 2007 on Limited Liability Company or hereinafter calledCompany Law of 2007 with the Law Number 1 of 1995 on Limited Liability Companyor hereinafter called Company Law of 1995". This journal addresses the problem ofhow the Board of Directors' responsibility reviewed based on the Company Law of 2007compared to the Company Law of 1995. It is a normative legal research that uses acomparative approach. The conclusion of the writing of this journal is that regarding tothe responsibility of Board of Directors, which now regulated by Company Law of2007, as originally stipulated on Company Law of 1995 turned out to have nosignificant differences. It is just that some of the articles provided in the Company Lawof 2007 give further clarify and expand the responsibilities of the Board of Directorsthan those mentioned in the previous Limited Liability Company Law of 1995.
Keywords: Directors, Responsibility, Limited Liability Company